Heliópolis (São Paulo): as intervenções públicas e as transformações na forma urbana da favela (1970 2011) - Souza, Vanessa Padiá de (2012)
This research discusses the slums urban forms and the impact of the public interventions. It seeks to understand the morphological elements that differentiate the precarious settlements, in this case the slums peculiarity in São Paulo. Taking Heliopolis community as a study case the discussion goes through since its origin in 1972, traversing the various public interventions at different political moments. It has the issue to comprehend the transformation process on its morphology and the impacts that occurs. The analysis of three projects Delamare Condominium (1989); Cingapura Heliopolis Sector A (1996); Social Housing 115 (2005) provides an understanding regarding breaks and contiguities of the slums urban form and what are the prospects that enable the integration and recognition of large settlements, as an inherent part of the city.